Forensic Efficiency Estimation of a Homemade Six-Color Fluorescence Multiplex Panel and In-Depth Anatomy of the Population Genetic Architecture in Two Tibetan Groups - Liu, Yanfang; Cui, Wei; Jin, Xiaoye; Wang, Kang; Mei, Shuyan; Zheng, Xingkai; Zhu, Bofeng (Frontiers in Genetics, 2022)
The genetic information of the Chinese Tibetan group has been a long-standing research hotspot among population geneticists and archaeologists. Herein, 309 unrelated individuals from two Tibetan groups living in Qinghai Province, China (CTQ), and Tibet Autonomous Region, China (CTT), were successfully genotyped using a new homemade six-color fluorescence multiplex panel, which contained 59 autosomal deletion/insertion polymorphisms (au-DIPs), two mini short tandem repeats (miniSTRs), two Y-chromosomal DIPs, and one Amelogenin. The cumulative probability of matching and combined power of exclusion values for this new panel in CTQ and CTT groups were 1.9253E-27 and 0.99999729, as well as 1.5061E-26 and 0.99999895, respectively. Subsequently, comprehensive population genetic analyses of Tibetan groups and reference populations were carried out based on the 59 au-DIPs. The multitudinous statistical analysis results supported that Tibetan groups have close genetic affinities with East Asian populations. These findings showed that this homemade system would be a powerful tool for forensic individual identification and paternity testing in Chinese Tibetan groups and give us an important insight for further perfecting the genetic landscape of Tibetan groups.